Childhood stroke in sickle cell disease in Nigeria - Lagunju, Ikeoluwa A.; Brown, Biobele J.; Famosaya, Abimbola A. (Journal of Pediatric Neurology, 2011)
Stroke is a devastating and potentially fatal complication of sickle cell disease (SCD). Children who survive a stroke attack are also at increased risk of motor disabilities, learning difficulties and epilepsy. The study was carried out to evaluate the prevalence and characteristics of stroke and its attendant complications in children with SCD seen at the University College Hospital, Ibadan, Nigeria. All consecutive cases of SCD that developed a stroke over a 4-year period were studied and followed up for a period of 1 year. Twenty-four of 351 children with SCD developed a stroke, giving a prevalence rate of 6.8%. The mean age at first stroke was 81.4 ± 37.2 months, 75% of children suffered the first stroke between the ages of 2 and 9 years. Ischemic stroke was the predominant form seen. The case fatality was 4.2%. Six (26.1%) of the 23 children who survived the first stroke had another attack of stroke within 1 year of the first stroke. The major long-term neurological sequelae were motor disabilities, dysphasia, learning disability and epilepsy. Stroke is a common neurological complication of SCD. Its prevalence in Nigerian children with SCD is not lower than what is reported in North America. The risk of recurrence after a first stroke remains high in the absence of preventive treatment. There is a need to explore other preventive measures apart from periodic blood transfusion to ameliorate the burden of stroke associated with SCD in a resource-poor country like Nigeria.
Keywords: Childhood; stroke; sickle cell disease